IDENTIFYING MODERATE VALUES IN THE TEXTBOOK OF SEJARAH KEBUDAYAAN ISLAM FOR THE 6TH GRADE OF MADRASAH IBTIDAIYAH IN INDONESIA - Sibawaihi, Sibawaihi; Altamimi, Mansour Ibrahim; Muqowim, Muqowim; Yap, Siti Nursheila Khairuddin (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2021)
The study investigates the implementation of the values of Islām wasaṭiyyah in the textbook of Sejarah Kebudayaan Islam for the 6th Grade of Madrasah Ibtidaiyah in Indonesia. By library research using content analysis, the authors conclude that the values of Islām wasaṭiyyah are very relevant to the character education that is currently being rolled out and promoted by the Indonesian government. There are nine values of Islām wasaṭiyyah demonstrated through the storytelling in the textbook: tawassuṭ (taking the middle path), tasāmuḥ (tolerance), musāwah (egalitarian/non-discrimination), shūrā (deliberations), i’tidāl (straight and firm), iṣlāḥ (reform), aulawiyyah (prioritizing priorities), taṭāwur wa ibtikār (dynamic and innovative), and taḥaḍḍur (civilized). The authors suggest that the textbook’s Core Competencies and Basic Competencies need to be expanded to cover all the values included in the story. In addition, proportionally, all the values need to be put because there is no value explained to be much more dominant than others.